2010
DOI: 10.1007/s10295-010-0724-7
|View full text |Cite
|
Sign up to set email alerts
|

Transient metabolic modeling of Escherichia coli MG1655 and MG1655 ΔackA-pta, ΔpoxB Δpppc ppc-p37 for recombinant β-galactosidase production

Abstract: Escherichia coli is one of the most widely used hosts for the production of recombinant proteins, among other reasons because its genetics are far better characterized than those of any other microorganism. To improve the understanding of recombinant protein synthesis in E. coli, the production of a model recombinant protein, beta-galactosidase, was studied in response to the constitutive overexpression of the anaplerotic reaction afforded by PEP carboxylase. To this end, an IPTG wash-in experiment was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…It is also possible to combine different strategies to reduce the formation of undesired by-products, including acetate. For example, one study found that a mutant E. coli strain containing a defective acetate pathway and an overexpressed phosphoenolpyruvate carboxylase-encoding ppC reduced acetate and other by-product formation and produced five time more β-galactosidase activity when compared the wild type strain (De Mey et al, 2010).…”
Section: Efforts In Product Improvements and Generation Of New Analogsmentioning
confidence: 99%
“…It is also possible to combine different strategies to reduce the formation of undesired by-products, including acetate. For example, one study found that a mutant E. coli strain containing a defective acetate pathway and an overexpressed phosphoenolpyruvate carboxylase-encoding ppC reduced acetate and other by-product formation and produced five time more β-galactosidase activity when compared the wild type strain (De Mey et al, 2010).…”
Section: Efforts In Product Improvements and Generation Of New Analogsmentioning
confidence: 99%
“…FK506 is likewise an immunosuppressive medicationas well as it was key exposed in soil trials holding Streptomyces tsukubaensis plus some additional Streptomyces types.FK506 is castoff to minimalize body partrefusal plus to persuade immunosuppression through calcineurin reticence too break of T cell activation pathway .It has established nearer additional actual than cyclosporine plus non poisonous in minute quantities . The detection of its immunosuppressive movement controlled toward its usage in heart, liver, also kidney transplants through irresistible accomplishment .Similar rapamycin, FK506 retains several biological events, as well as antifungal, anti inflammatory, neuron protective, alsoneuron reformative actions [16].…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%